Ultra Low-Dose Naloxone and Tramadol/Acetaminophen in Elderly Patients Undergoing Joint Replacement Surgery: A Pilot Study - Ngozi N Imasogie; Sudha Singh; James T Watson; Debbie Hurley; Patricia Morley-Forster (Pain Research and Management)
OBJECTIVE: A pilot study was conducted to assess whether both the rationale and feasibility exist for future randomized clinical trials to evaluate the combined use of naloxone infusion and tramadol/acetaminophen as opioid-sparing drugs in elderly patients undergoing lower extremity joint replacement surgery.